From financial structure to economic growth: Theory, evidence and challenges. (19th November 2021) - Xu, Guangdong
Abstract: This paper surveys the theoretical and empirical literature on the contributions of financial structure to economic growth. Whereas the theoretical literature clarifies the channels through which banks and financial markets may affect resource allocation and hence economic performance, the empirical evidence on the connection between financial structure and economic growth is mixed. There are several methodological problems inherent in the literature, including disparate studies that have been frequently mixed and confused, unsolved econometric issues (endogeneity, heterogeneity and omitted variables) and failure to consider the interaction between banks and capital markets. More rigorous single‐country studies are called for.